Correlation Between VO2 Max, Speed, and Limb Muscle Explosive Power with Agility in Soccer Players - Himmatul Aulia, annisa; Widodo, Sumardi; Indraswari, Darmawati Ayu; Adyaksa, Gana (Faculty of Medicine, Diponegoro University, 2023)
Background: Agility is one of football's most critical anaerobic capacities. One component is the ability to change direction. Players change direction (Change of direction speed / CODS) every 2-4 seconds. Agility is influenced by several things, including speed and limb muscle explosive power, and is related to aerobic capacity, namely VO2 Max (maximum oxygen consumption) in the Running economy aspect. It is necessary to research the relationship between VO2 Max, speed, and explosive power of limb muscles with agility in soccer playersObjective: Knowing correlation between VO2 Max, speed, and limb muscle explosive power with agility in soccer players.Methods: Twenty-seven male players (Diponegoro Muda PS Undip) were involved in this study (mean±SD; age 13.22 ± 0.18 years, weight 46.78 ±1.67 kg, height 158± 1.88 cm). This research is a correlational study using a cross-sectional design. Each player will be measured VO2 Max with the Multistage Fitness Test, speed with the 20-meter sprint test, the explosive power of the limb muscles with the surgent jump test, and agility (CODS) using the Illinois agility test. The hypothesis test used is Spearman's hypothesis test and linear regression test.Results: Spearman correlation test found a strong relationship between VO2 Max and agility (r=-0.743; p= <0.001), there was a moderate relationship between speed and agility (r=0.556; p== 0.003), there was a strong relationship between muscle explosive power limbs with agility (r=-0.766; p= <0.001), and the results of linear regression of variables VO2 Max, speed, limb muscle explosive power on agility showed a strong relationship (r=0.806; r2= 0.650; p=<0.001).Conclusion: Conclusions: VO2 Max correlates with agility; speed correlates with agility; limb muscle explosive power correlates with agility; and the variables of VO2 Max, speed, and limb muscle explosive power have a relationship with agility.